Good Practices for Courts : Helpful Elements for Good Court Performance and the World Bank’s Quality of Judicial Process Indicators - Gramckow, Heike (World Bank, Washington, DC, 2016)
As the SDGs become reality, countries continue to seek for options to meet the new goals and to keep track of their progress. This includes efforts related to the new Goal 16, “Justice and Peace”. Achieving the SDGs requires implementation in many areas. Today, courts in many countries are undergoing reforms, are interested in hearing about new trends in court operations elsewhere and in tracking court performance. The World Bank’s new publication “Good Practice for Courts—Helpful Elements for Good Court Performance and the World Bank’s Quality of Judicial Process Indicator (QJPI)” addresses this desire. Focusing on the 15 QJPI good practice areas, the publication reflects the findings from country studies and other reports from around the world that show how modern management approaches and advanced technologies provide new opportunities for courts and other justice sector agencies to modernize their operations to better reflect the changing needs of their communities as well as those of national and international markets. Simultaneously, the OECD, in collaboration with the Open Society Foundation, are focusing on collecting and highlighting innovative country approaches to promote access to legal and justice services as determinant of inclusive growth and contributor to the realization of Sustainable Development Goals.